Model Spasial Terhadap Faktor yang Mempengaruhi Keberadaan Kambing Hutan Sumatera [Capricornis sumatraensis sumatraensis pechstein, 1799)l di Wilayah Sipurak, Taman Nasional Kerinci Seblat, Jambi - Susanti, Neneng (Perhimpunan Biologi Indonesia, 2007)
ABSTRACTSpatial Modelling Impact for Sumatran Serow Occupancy [Capricornissumatmensissumatraensis (Bechsteiu, 1799)] at Sipurak-Kerinci Seblat National Park, Jambi.Existency for habitat preference of sumatran serow is very important to support the wildlifemanagement. The research was designed to study the influence of factor of spatialhabitat occupany or habitat preference of sumatran serow [Copricornis sumatraensisAbstractsumotraensis (Bechstein, 1799)l. The detection-non detection survey method was appliedfor observation. Data processed by using software Arcview 3.2, and PRESENCE PC.From the ten model selected, there was little variation in the estimates of occupancy (Y )IPA0 (ranging from 0,7283 to 0,7637) and detection probability orp (0,2407 to 0,2495).The top two ranked models are distance to forest and slope. Its mean th%t distance toforest and slope have good influence on occupancy of Sumatran serow. The factors ofspatial habitat have positive correlation to PAO. Sumatran serow occupancy was greaterin grid cells that were further from the forest edge, in grid cells that were located onsteeper slopes, and also from others spatial habitat factors.Key words: The factor of spatial habitat; sumatran serow; PAO; detection probability; Sipurak.